Kemampuan Pedagogik Mahasiswa PPG Daljab dalam Pengembangan Video Pembelajaran - Bambang Sulistyo; Darningwati Darningwati; Nurhasanah Nurhasanah; Henny Yulia; Nora Agustina (Balai Bahasa Sulawesi Selatan, 2026)
This study aims to describe the pedagogical competence of in-service Teacher Professional Education (PPG Daljab) students in Indonesian Language Education in developing learning videos for the Performance Assessment of PPG Daljab Batch 5. The study employed a descriptive quantitative approach involving 48 students as research subjects. Data were collected through an assessment of learning videos using a pedagogical competence rubric covering alignment with the lesson plan, lesson opening, material presentation, instructional strategies and interaction, media use, language and intonation, and lesson closure and reflection. The results indicate that, classically, students’ pedagogical competence ranged from good to very good. The lesson opening aspect achieved a very good category, while instructional strategies and interaction as well as media use were categorized as sufficient. These findings suggest that PPG Daljab students possess adequate pedagogical competence in developing learning videos; however, improvements are still needed in enhancing interactivity and optimizing digital media use. This study provides implications for strengthening pedagogical development in the PPG Daljab program. AbstrakArtikel ini bertujuan untuk mendeskripsikan kemampuan pedagogik mahasiswa Pendidikan Profesi Guru (PPG) Dalam Jabatan (Daljab) Bidang Studi Pendidikan Bahasa Indonesia dalam pengembangan video pembelajaran pada Ujian Kinerja PPG Daljab Gelombang 5. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan subjek penelitian sebanyak 48 mahasiswa. Data dikumpulkan melalui penilaian video pembelajaran menggunakan rubrik kemampuan pedagogik yang mencakup kesesuaian dengan modul, pembukaan pembelajaran, penyajian materi, strategi dan interaksi, penggunaan media, bahasa dan intonasi, serta penutup dan refleksi. Hasil penelitian menunjukkan bahwa secara klasikal kemampuan pedagogik mahasiswa berada pada kategori baik hingga sangat baik. Aspek pembukaan pembelajaran memperoleh kategori sangat baik, sementara aspek strategi dan interaksi serta penggunaan media berada pada kategori cukup. Temuan ini menunjukkan bahwa mahasiswa PPG Daljab telah memiliki kompetensi pedagogik yang memadai dalam pengembangan video pembelajaran, namun masih memerlukan penguatan pada aspek interaktivitas dan pemanfaatan media digital. Penelitian ini berimplikasi pada pengembangan kebijakan dan praktik pembinaan pedagogik dalam program PPG Daljab.